El Estado nacional y los indígenas: el caso de Talamanca y Guatuso Costa Rica, 1821-1910 - Boza Villarreal, Alejandra; Solórzano Fonseca, Juan Carlos (Revista de historia., 2000)
The author explores how and when coffee consumption developed in Costa Rican society in order to determine the relationship between coffee consumption, sociability, and identity, and highlight the factor which contributed  to the growth of domestic consumption.